2019
DOI: 10.1093/hropen/hoz015
|View full text |Cite
|
Sign up to set email alerts
|

Tubal flushing with oil- or water-based contrast medium: can we identify markers that indicate treatment benefit?

Abstract: STUDY QUESTION Can we identify patient characteristics that distinguish which ovulatory infertile women undergoing hysterosalpingography (HSG) benefit more or less from flushing with oil-based contrast medium compared to water-based contrast medium? SUMMARY ANSWER In ovulatory infertile women, HSG with oil-based contrast medium resulted in higher 6-month ongoing pregnancy and live birth rates as compared to HSG with water-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The trial included women aged 18‐39 who had been trying to conceive for at least one year with low risk of tubal pathology and in whom tubal patency testing was indicated. A secondary analysis aimed to determine which subgroups would most benefit and found that all women <39 years were likely to benefit but postulated additional value for lean women, smokers and those with male partners who have ejaculate volume >3 mL 9 . Weak data also raise the possibility that women with endometriosis may particularly benefit and further studies in this group were recommended 3 …”
Section: Resultsmentioning
confidence: 99%
“…The trial included women aged 18‐39 who had been trying to conceive for at least one year with low risk of tubal pathology and in whom tubal patency testing was indicated. A secondary analysis aimed to determine which subgroups would most benefit and found that all women <39 years were likely to benefit but postulated additional value for lean women, smokers and those with male partners who have ejaculate volume >3 mL 9 . Weak data also raise the possibility that women with endometriosis may particularly benefit and further studies in this group were recommended 3 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore the higher VAS score in the HSG procedure as compared to the subsequent HyFoSy procedure in this study was not biased by psychological factor of expecting pain in the subsequent procedure [17]. In regard to possible therapeutic effect of conventional HSG that may have altered the findings on HyFoSy, the studies on the effect of tubal flushing with HSG to increase live birth rate had a low quality of evidence [18]. Therefore, conventional HSG was not likely to have altered the findings on HyFoSy in our study.…”
Section: Discussionmentioning
confidence: 82%
“…However, to select the best treatment for an individual patient it is important to quantify the benefit of one treatment over the other [ 8 ]. Previous marker-by-treatment analysis provided clinicians an evidence based method to select the best treatment for ovulatory infertile women [ 30 ]. In middle aged and older patients with a meniscal tear, the results from RCTs show that meniscal surgery has no clinical advantage over non-surgical treatment (such as physical therapy) or placebo surgery.…”
Section: Introductionmentioning
confidence: 99%